2020
DOI: 10.1111/tbed.13890
|View full text |Cite
|
Sign up to set email alerts
|

Joining the club: First detection of African swine fever in wild boar in Germany

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
101
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 22 publications
1
101
1
Order By: Relevance
“…In our hands, this matrix was not practicable. Ear punches of clinically diseased animals were positive for viral genome which is in line with recent findings that also show the skin yielded positive results when testing wild boar carcasses [ 40 ] or experimentally infected animals [ 17 ]. However, the low level of viral genome and the quite difficult handling does not make this matrix an alternative candidate for routine settings.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our hands, this matrix was not practicable. Ear punches of clinically diseased animals were positive for viral genome which is in line with recent findings that also show the skin yielded positive results when testing wild boar carcasses [ 40 ] or experimentally infected animals [ 17 ]. However, the low level of viral genome and the quite difficult handling does not make this matrix an alternative candidate for routine settings.…”
Section: Discussionsupporting
confidence: 86%
“…Over the last years, our group has validated blood swabs as an alternative matrix for passive surveillance, especially in wild boar [ 11 , 12 , 23 ]. Only recently, the approach was also put to field practice when ASF entered Germany, and it performed well [ 40 ]. As optimization is always possible, and new development have been put on the market, we include a new type of swab and transport buffer into our comparison.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they can carry diseases, which may threaten livestock animals. In particular, the first detection of African swine fever virus in wild boars hunted in Germany near the border to Poland in 2020 has raised serious concerns about a transmission to domestic pigs [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recent entry of African swine fever (ASF) into Germany in September 2020 showed that the ASF spread in the European Union has not yet come to a hold (1). Since the beginning of the current epidemic in Georgia in 2007, more and more wild boar and domestic pigs have become infected globally (2).…”
Section: Introductionmentioning
confidence: 99%